2004
DOI: 10.1002/mde.1184
|View full text |Cite
|
Sign up to set email alerts
|

The economics of managerialism and the drive for efficiency in policing

Abstract: The UK has recently proposed to develop a set of criteria whereby the economic analysis of police force efficiency is to be made standard. This follows a strategy of aiming for improvement through managerialism and best value performance indicators, similar to those implemented by US police forces after the Government Performance and Results Act 1993. In this paper we attempt to put this recent development of efficiency targeting into a UK historical|evolutionary context and provide one of the first attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Because of the agreements to keep details that could identify the force concerned confidential, further contextual information on geography, policing demands and specific HR issues cannot be provided here. However it can be said that this police force had typical county policing demands that included city populations and large rural areas and in performance terms is a middle ranking police force (Drake and Simper 2004). The survey data was tested for evidence of respondent fatigue (that is, inconsistent responses to similar questions in different parts of the questionnaire) and it was concluded that a bias of this kind was not present.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the agreements to keep details that could identify the force concerned confidential, further contextual information on geography, policing demands and specific HR issues cannot be provided here. However it can be said that this police force had typical county policing demands that included city populations and large rural areas and in performance terms is a middle ranking police force (Drake and Simper 2004). The survey data was tested for evidence of respondent fatigue (that is, inconsistent responses to similar questions in different parts of the questionnaire) and it was concluded that a bias of this kind was not present.…”
Section: Methodsmentioning
confidence: 99%
“…DEA has been applied extensively in the last 40 years (Emrouznejad & Yang, 2017). It has been adopted to study the performance of public institutions such as, for example, health care (e.g., Mitropoulos, Talias, & Mitropoulos, 2015;Pulina, Detotto, & Paba, 2010), the police forces (e.g., Drake & Simper, 2004), universities (e.g., Fandel, 2007), as well as the judiciary (e.g., Peyrache & Zago, 2016;Santos & Amado, 2014). This is a non-parametric technique that allows efficiency performance to be measured as a score (Cook & Seiford, 2009), implementing a benchmark analysis.…”
Section: Data Envelopment Analysis (Dea)mentioning
confidence: 99%
“…DEA is an appropriate technique for determining the relative efficiency of public organizations (Athanassopoulos & Curram, 1996;Camanho & Dyson, 1999;Ludwin and Guthrie, 1989;Nyhan, 2002;Nyhan & Martin, 1999a). This methodology has been applied extensively to measure police department efficiency in the United States (Goltz, 2006;Moore, Nolan, & Segal, 2005;Nyhan and Martin, 1999b), the United Kingdom (Carrington, Puthucheary, Rose, & Yaisawarng, 1997;Drake and Simper, 2004, 2001Thanassoulis, 1995), Portugal (Barros, 2007), Spain (Diez-Ticio & Mancebon, 2002;Garcia-Sanchez, 2009, Taiwan (Sun, 2002), and India (Verma & Gavirneni, 2006). None of these studies have compared university departments with either their local municipal or functional university counterparts: this study does both to enhance and to extend the police efficiency literature.…”
Section: Campus Police In Floridamentioning
confidence: 99%